2022
DOI: 10.1186/s40798-022-00515-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity During Lockdowns Associated with the COVID-19 Pandemic: A Systematic Review and Multilevel Meta-analysis of 173 Studies with 320,636 Participants

Abstract: Background Many countries have restricted public life in order to contain the spread of the novel coronavirus (SARS-CoV2). As a side effect of related measures, physical activity (PA) levels may have decreased. Objective We aimed (1) to quantify changes in PA and (2) to identify variables potentially predicting PA reductions. Methods A systematic review with random-effects multilevel meta-analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
13
0
3
Order By: Relevance
“…This study confirmed reductions in physical fitness parameters due to reduced physical activity [ 8 , 9 , 47 ], as participants were not allowed to perform regular training within the intervention, with the exception of daily stretching (IG). While there were significant increases in performance with MVC90, KtW and SJ height , no significant changes could be determined in CMJ height and DJ height , CT and RSI in response to stretching.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This study confirmed reductions in physical fitness parameters due to reduced physical activity [ 8 , 9 , 47 ], as participants were not allowed to perform regular training within the intervention, with the exception of daily stretching (IG). While there were significant increases in performance with MVC90, KtW and SJ height , no significant changes could be determined in CMJ height and DJ height , CT and RSI in response to stretching.…”
Section: Discussionsupporting
confidence: 57%
“…Physical inactivity is a consistent part of many people’s daily life [ 1 ], as well as the possibility for prolonged phases of immobilization [ 2 , 3 , 4 ], which can have significant negative influences on metabolic and musculoskeletal health [ 5 , 6 ] in sports performance. In addition to injuries and frequent sitting, evidence highlights significantly decreased physical activity and motivation to train [ 7 ] in the majority of people due to the COVID-19 lockdown(s) [ 8 , 9 , 10 ]. As a consequence, reduced physical fitness, including strength capacity and maximal strength (MSt), were reported.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 173 studies revealed that, during COVID-19 lockdowns, physical activity decreased and sedentary behavior increased at the same time [43]. Another study from South Africa showed that moderate to high levels of physical activity may have significant benefits especially in preventing negative outcomes of COVID-19, such as hospitalization, ICU admission, ventilation and death [44]. We found that 21.9% of older people engaged in at least 2 h (120 min) of physical activity per week.…”
Section: Discussionmentioning
confidence: 99%
“…Although Taiwan did not have a large-scale lockdown compared with other parts of the world, Level 3 alert restrictions, such as shutting most business and public places, banning group gatherings and physical activities in open spaces, gyms, and sports centers, may still have created a barrier to maintaining exercise behavior among Taiwanese individuals [7]. While public life restrictions associated with the pandemic were usually of a limited duration, some studies have shown that even a short-term increase in physical inactivity and sedentary behavior can have significant adverse effects [29]. For example, 14 days of step reduction can lead to insulin resistance as well as increased central and liver fat and dyslipidemia, while reducing cardiorespiratory fitness [30].…”
Section: Discussionmentioning
confidence: 99%